THE DIFFERENCES BETWEEN PRAGMATIC AND IDEOLOGICAL LEADERSHIP IN ORGANIZATION: A SYSTEMATIC LITERATURE REVIEW - Danny Philipe Bukidz; Genesis Sembiring Depari; Elisabeth Marlina Sari Lintong (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Introduction/Main Objectives: This study aims to analyze and compare existing literature on pragmatic and idealistic leadership, specifically examining the differences between these leadership styles within organizations. The goal is to develop a more comprehensive understanding of these two approaches and how they contrast with one another. Background Problems: The research may face background challenges due to inadequate understanding of the differences between pragmatic and idealistic leadership, as well as the advantages and disadvantages of each style. Moreover, it may be necessary to investigate the perceptions of various stakeholders such as followers, peers, and superiors towards these leadership styles. Novelty: Prior research has predominantly examined these leadership styles in isolation ; however, this study seeks to present a more comprehensive analysis by exploring both their distinctions and commonalities. Research Methods: A Systematic Literature Review is expected to include an analysis of existing studies sourced from five reputable journals indexed in the scopus database. Finding/Results: Pragmatic leadership is flexible and adaptable, emphasizing context-dependent approaches that prioritize relationships within a community. Ideological leadership, on the other hand, involves leaders who have a strong belief in a particular ideology or set of values that guide their decision-making and actions. Conclusion: the articles suggest that modern leaders need to be both pragmatic and idealistic to succeed. They should have a strong belief in their vision or set of values while also being flexible and adaptable to the current situation.